The importance of trauma-informed approaches in education – the impact of implementing a brain-based approach to supporting learners across a Scottish Local Authority - Lesley Taylor; Whitney Barrett (International Journal of School Social Work, 2022)
Throughout the history of education, a series of fashions, fads and trends has come and gone – some resulting in widespread changes in approach, some creating barely a ripple in the "pedagogical pool". Currently, a wave is being created by the desire to develop approaches that are trauma-informed – a move that is being driven by a number of factors including the introduction of funding streams such as the Scottish Attainment Challenge (SAC) and the Pupil Equity Fund (PEF), alongside growing public awareness of the impact childhood trauma and adversity has across many areas of a child’s development. However, we have previously warned (Barrett, 2018) of the pitfalls associated with the "grass roots" movement that has arisen across Scotland in recent years which has, in our opinion, been at risk of over-simplifying incredibly complex, deep-rooted societal issues that go far beyond the realm of education. We have, therefore, welcomed the more nuanced approach that has developed within the movement as the focus has shifted to become more acknowledging of the complexity and multitude of factors involved in childhood trauma and adversity The social-political context of childhood adversity and trauma means solutions to such a complex problem need to be sought within arenas far removed from education - such as government legislature and economic policy. These changes are both long term in nature, meaning the enduring effects of these experiences will continue to be felt for generations to come. It is crucial, therefore, that schools and other educational establishments are able to adapt their environments and teaching practices to meet the increasingly complex needs of the learners coming through their doors. This study will describe a small-scale project which sought to gather standardised evidence of the impact of the Readiness for Learning (R4L) approach we have developed as part of a wider evaluation approach. The R4L approach combines a range of theories to develop procedures that encourage BALTIC practice – Brain-Based, Attachment-Led, Trauma-Informed and Community-based. The approach is heavily influenced by the Neurosequential Model in Education (Bruce Perry, e.g. Perry, 2013), as well as the work of John Bowlby and Mary Ainsworth (Bowlby, 1969) (Ainsworth and Bell, 1970), Dan Siegel (e.g. Siegel, 2001), Francine Shapiro (e.g. EMDR.com, 2018), Dan Hughes (e.g. Hughes, pers. Comm. 31st October 2017) and Urie Bronfenbrenner (Bronfenbrenner, 1979). This study focuses on the implementation of R4L within a targeted population of Primary One (4/5 year olds) and the impact that it had on a range of standardised performance measures up until the March of their Primary Three year. Further information on the wider development and implementation of the approach can be found in Taylor and Barrett (2018). We will conclude by offering some wider reflections on the need for trauma-informed approaches within education, and the conditions we believe need to be in place for these to be successful.
Keywords: trauma; child abuse; teacher-student relationships; school mental health; school social work